1959
DOI: 10.1002/hlca.19590420639
|View full text |Cite
|
Sign up to set email alerts
|

Über die Bestimmung von Porengrössen

Abstract: Volurnen XLII, Fasciculus VI (1959) -No. 226-227 2103 in which the structure of I1 was systematically modified, i. E. psilocin derivatives with other substitution at the w-nitrogen; derivatives of I1 substituted at the indole nitrogen; psilocin derivatives with one additional methylene group in the sidechain or with a methyl-substituted or hydroxylated side-chain ; phosphoric acid esters of some derivatives of 11; esters of I1 with organic carbonic and sulfonic acids, with methylcarbaminic and with sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1962
1962
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…White (16,17,18) has recently reviewed fluorometric methods. Several sensitive fluorometric methods utilize morin (3,5,7,2',4'-pentahydroxyflavone) (16), Pontachrome Blue Black R (sodium salt of 4-sulfo-2-hydroxy-l-naphthylazo-2'-naphthol) (14), 8-quinolinol (7), salicylaldehyde condensation products (9), and various hydroxyazo dyes. Colorimetric and fluorometric methods for the determination of beryllium have been reviewed by Sandell (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…White (16,17,18) has recently reviewed fluorometric methods. Several sensitive fluorometric methods utilize morin (3,5,7,2',4'-pentahydroxyflavone) (16), Pontachrome Blue Black R (sodium salt of 4-sulfo-2-hydroxy-l-naphthylazo-2'-naphthol) (14), 8-quinolinol (7), salicylaldehyde condensation products (9), and various hydroxyazo dyes. Colorimetric and fluorometric methods for the determination of beryllium have been reviewed by Sandell (11).…”
Section: Resultsmentioning
confidence: 99%
“…Another method, developed by Ritter and Drake (21), is based on the penetration of a nonwetting liquid, such as mercury, under pressure. An automatic mercury penetrometer was devised by Guyer (14) and commercialized. With this technique it is necessary to produce very high pressures; for pores of 150-A.…”
mentioning
confidence: 99%
“…Experiments are usually carried out with N 2 at 77 K, or with other simple gases adsorbed near their normal boiling point temperature. Since this technique covers the range of 2-50 rim, there is an interesting overlap with mercury porosimetry, providing a check for consistency [6]. In the case of carbon U, for example, it is found that there exists a significant mesoporosity in the range of 2.5 to 4.5 nm, which amounts to 0.45 cm3/g.…”
Section: Figurementioning
confidence: 98%
“…By using well-known experimental techniques and the equation of Kelvin [5], it is possible to characterize effectively the range of porosity (b). Macroporosity and the major part of mesoporosity can be investigated by mercury porosimetry [6], which covers approximately the range of 5-7500 nm, depending on the experimental conditions. This method is based on the relation which exists between the external pressure p and the radius rp of the smallest pores being filled by mercury, r, = (27/p) cos ~…”
Section: The Porosity Of Activated Carbons In Generalmentioning
confidence: 99%
“…El procedimiento del porosímetro de mercurio ha sido descrito por numerosos autores (2), ( 4), (7). El esquema del procedimiento así como el desarrollo de su utilización se halla descrito en la figura 1.…”
Section: Fig 1-esquema Del Porosimetro De Mercurio Para (Según K Nies...unclassified